Effects of International E-Commerce Firms' Depth versus Breadth of Control on Foreign Sales Performance and the Role of Market Size and Growth as Context Factors - Marius Mueller; Bernhard Swoboda (Management International Review, 2025)
E-commerce firms (ECFs) are known to internationalize digitally but may also opt for high international control in terms of depth (i.e., by choosing fully controlled operation modes to enable local offers and management) or breadth (i.e., through a subsidiary network to scale their business model and supply chain). Surprisingly, little is known about the role of ECFs' international control decisions in foreign performance or how these decisions are affected by dynamic e-commerce market contexts. To address these gaps, the authors explore the effects of ECFs' depth and breadth of control on foreign sales performance and the role of local~e-commerce market size and growth as context factors. They refer to unique secondary data on 1,144 control decisions by 184 leading ECFs over time and apply multilevel modeling. The results show that ECFs generally improve foreign sales performance by choosing both higher depth and breadth of international control. However, these firms face trade-offs because both decisions affect performance differently and market growth moderates the effects positively and negatively. This allows direct implications for firms expanding digitally abroad but possibly struggling with sales performance.
Keywords: 330; E-Commerce firms; Foreign sales performance; Degree of control; Market size; Market growth; Multilevel modeling